NON-LINEAR ANALYSIS OF BEAM-COLUMN JOINTS WITH GEOPOLYMER: A SUSTAINABLE APPROACH TO REINFORCED CONCRETE CONSTRUCTION (International Journal of Engineering Management Science, 2024)
This paper presents a study on the non-linear analysis of beam-column joints with geopolymer, focusing on their behavior under various loading conditions. Geopolymer, as an alternative material in construction, offers several advantages over traditional Portland cement, including lower carbon footprint and higher chemical resistance. However, its use in critical structural elements like beam column joints is still limited, primarily due to a lack of understanding of its behavior under non-linear loading.The study utilizes finite element modeling to analyze the performance of beam-column joints with geopolymer, considering factors such as material properties, joint geometry, and loading conditions. The results indicate that geopolymer shows promising potential in beam-column joints, with comparable or superior performance to traditional concrete. The analysis highlights the importance of non-linear analysis in accurately predicting the behavior of these joints and suggests future research directions in this area.
Keywords: Geopolymer, beam-column joints, non-linear analysis, finite element modeling, reinforced concrete, sustainability